A review of the Philippine Campsosternus (Coleoptera: Elateridae), with descriptions of new taxa - Vanags, Artūrs (Zootaxa, 2026)
A review of the Philippine species of Campsosternus Latreille, 1834 (Coleoptera: Elateridae) is presented. Campsosternus mindorensis sp. nov. is described from Mindoro. It differs from all previously known Philippine species of Campsosternus by the presence of dense pubescence on both dorsal and ventral parts of the thorax, a feature not observed in any previously described species from the archipelago. Besides that, two new subspecies are described and illustrated: C. rutilans mindanaoensis ssp. nov. (Mindanao) and C. r. cupreus ssp. nov. (Panay, Negros). Morphological variation among island populations for these taxa is interpreted as intraspecific geographic differentiation. Two new synonymies are proposed: C. rutilans Chevrolat, 1841 = C. proteus Hope, 1843, syn. nov.; C. leachii Hope, 1843 = C. eschscholtzii Hope, 1843, syn. nov. A key to the Philippine species and subspecies is included.